HOC24
Lớp học
Môn học
Chủ đề / Chương
Bài học
Ta có: \(\frac{x-1}{2}=\frac{y-2}{3}=\frac{z-3}{4}\)
\(\Rightarrow\frac{x-1}{2}=\frac{2\left(y-2\right)}{6}=\frac{3\left(z-3\right)}{12}\)
hay \(\frac{x-1}{2}=\frac{2y-4}{6}=\frac{3z-9}{12}\)
Áp dụng dãy tỉ số bằng nhau, ta có:
\(\frac{x-1}{2}=\frac{2y-4}{6}=\frac{3z-9}{12}=\frac{x-1-\left(2y-4\right)+3z-9}{2-6+12}=\frac{\left(x-2y+3z\right)-\left(9+1-4\right)}{8}=\frac{14-6}{8}=1\)
\(\Rightarrow x-1=2\Rightarrow2+1=3\)
\(\Rightarrow y-2=3\Rightarrow3+2=5\)
\(\Rightarrow z-3=4\Rightarrow4+3=7\)
Vậy \(\left(x;y;z\right)=\left(3;5;7\right)\)
bn nhấn vào câu hỏi tương tự
có mấy câu giống bài này